The Seven Sisters Versus Opec: Solving the Mystery of the Petroleum Market Structure - Noguera-Santaella, J (Elsevier B.V., 2017)
This paper provides an explanation of the changing behavior of the crude oil market and tests it using the U.S. data from January 1913 to September 2014. We claim that the crude oil market has experienced two important structural breaks in its industrial organization. The first occurred when Venezuela and the Arab crude oil exporting countries forced the so-called Seven Sisters to sign the Fifty–Fifty profit-sharing agreements. The second occurred after OPEC succeeded in cracking the secrets of the international crude oil marketing and in undertaking the wave of nationalizations of the 1970s. © 2017 Elsevier B.V.